Preparation of highly conductive graphene-coated glass fibers by sol-gel and dip-coating method. Issue 9 (September 2019) - Fang, Minghe; Xiong, Xuhai; Hao, Yabin; Zhang, Tengxin; Wang, Han; Cheng, Hui-Ming; Zeng, You
Abstract: In order to fabricate highly-conductive glass fibers using graphene as multi-functional coatings, we reported the preparation of graphene-coated glass fibers with high electrical conductivity through sol-gel and dip-coating technique in a simple way. Graphene oxide (GO) was partially reduced to graphene hydrosol, and then glass fibers were dipped and coated with the reduced GO (rGO). After repeated sol-gel and dip-coating treatment, the glass fibers were fully covered with rGO coatings, and consequently exhibited increased hydrophobicity and high electrical conductivity. The graphene-coated fibers exhibited good electrical conductivity of 24.9 S/cm, being higher than that of other nanocarbon-coated fibers and commercial carbon fibers, which is mainly attributed to the high intrinsic electrical conductivity of rGO and full coverage of fiber surfaces. The wettability and electrical conductivity of the coated fibers strongly depended on the dip-coating times and coating thickness, which is closely associated with coverage degree and compact structure of the graphene coatings. By virtue of high conductivity and easy operation, the graphene-coated glass fibers have great potential to be used as flexible conductive wires, highly-sensitive sensors, and multi-functional fibers in many fields.